Coinfection by Cetacean morbillivirus and Aspergillus fumigatus in a juvenile bottlenose dolphin (Tursiops truncatus) in the Gulf of Mexico. (November 2016) - Cassle, Stephen E.; Landrau-Giovannetti, Nelmarie; Farina, Lisa L.; Leone, Angelique; Wellehan, James F. X.; Stacy, Nicole I.; Thompson, Patrick; Herring, Hada; Mase-Guthrie, Blair; Blas-Machado, Uriel; Saliki, Jeremiah T.; Walsh, Michael T.; et al.
A recently deceased juvenile male bottlenose dolphin ( Tursiops truncatus ) was found floating in the Gulf of Mexico, off Sand Key in Clearwater, Florida. At autopsy, we identified pneumonia and a focus of malacia in the right cerebrum. Cytologic evaluation of tissue imprints from the right cerebrum revealed fungal hyphae. Fungal cultures of the lung and brain yielded Aspergillus fumigatus, which was confirmed by amplification of a portion of the fungal nuclear ribosomal internal transcribed spacer 2 region sequence. Microscopic pulmonary lesions of bronchiolar epithelial cell syncytia with intracytoplasmic and intranuclear inclusions within bronchiolar epithelial cells were suggestive of Cetacean morbillivirus (CeMV) infection. The occurrence of CeMV infection was supported by positive immunohistochemical staining for morbillivirus antigen. CeMV detection was confirmed by amplification and sequencing a portion of the morbilliviral RNA-dependent RNA polymerase gene from lung tissue. This case provides CeMV sequence data available from the Gulf of Mexico and underscores the need for genomic sequencing across diverse host, temporospatial, and population (i.e., single animal vs. mass mortality events) scales to improve our understanding of these globally emerging pathogens.